Mafia Firms and Aftermaths - Maria Rosaria Alfano; Claudia Cantabene; Damiano Bruno Silipo (ZBW – Leibniz Information Centre for Economics, 2019)
We use a unique and unexplored dataset to investigate the determinants and effects of mafia firms in Italy. Mafia may use several tools to expand its firms. However, in this paper, we show that they prefer political corruption to violence to expand mafia firms. In particular, they use the latter more to build up their reputation in new established regions. Mafia firms hamper entrepreneurial activity but they can have beneficial effects on unemployment if mafia firms add to not substitute current economic activities. Policy makers should take account of this twofold effects of mafia firms.
Keywords: D02; K14; L11; 330; Organized crime; Mafia firm; Mafia and development